Robust approach for efficiency measurement of employee performance under profit sharing system - Umi Mahmudah; Muhamad Safiih Lola (Economic Journal of Emerging Markets, 2018)
This study estimates the efficiency of employees’ performances under profitsharing system using data envelopment analysis (DEA). This method is one of themost common methods used in efficiency measurement analysis. However, arobust approach is used to deal with the complexity of the traditional DEAestimators. Robust Data Envelopment Analysis (RDEA) is very useful whenoutliers contaminate the data. The sample includes five divisions which cover asmany as 102 employees of a shipping company in Malaysia are analyzed by usingR program. The results reveal that the initial DEA efficiency is an over-estimate ofthe true efficiency. RDEA provides better accuracy of the results. Further, therobust approach is appropriate to be used in the measurement of the efficiency ofcompany divisions under profit sharing program.